Drosophila melanogaster: A model to study obesity effects on genes expression and developmental changes on descendants. - de Paula, M.T.; Silva, M.R.P.; Araújo, S.M.; Bortolotto, V.C.; Martins, I.K.; Macedo, G.E.; Franco, J.L.; Posser, T.; Prigol, M. (Journal of Cellular Biochemistry, 2018)
Maternal obesity and metabolic diseases are two of the most important potential dangers to offspring, given that impaired offspring may cause deficiencies that impair the adult life and health. This study evaluated the oxidative damage, the enzymatic antioxidant defenses, and the enzymes of fatty acid metabolism, such as Acyl-CoA Synthetase and Acetyl-CoA Synthetase (mRNA expression levels), as well as the modulation of cell stress signaling pathway, as Hsp83, and gene expression and insulin-like peptide DILP6 in Drosophila melanogaster models that received a high fat diet (HFD) (10% and 20% of coconut oil) throughout their development period. After 7 days, the progenitor flies were removed and, the remaining eggs were monitored daily, until the eclosion. The descendants were then exposed to a regular diet (RD). The results revealed that the HFD caused a decrease in the proportion of eclosion, lifespan, MTT reduction in mitochondrial enriched fractions, AceCS1 levels, mRNA expression levels (SOD and CAT), and in catalase activity a decrease was only observed in the group that received the highest concentration of coconut oil. In parallel, it was demonstrated an increase in the upregulation of HSP83 mRNA levels, but only when 10% of coconut oil was added, and an increase in glucose and triglyceride levels, as well as in DILP6 mRNA levels in larger concentration of coconut oil tested (20%). In conclusion, flies that have progenitors fed with HFD can develop metabolic dysfunctions, causing oxidative insults, which are involved in the shortening of lifespan.